Unveiling the circumstellar environment toward a massive young stellar object - Paron, Sergio Ariel (2013)
Aims: As a continuation of a previous work, in which we found strong evidence of massive molecular outflows toward a massive star-forming site, we present a new study of this region based on very high angular resolution observations with the aim of discovering the outflow-driven mechanism. Methods: Using near-IR data acquired with Gemini-NIRI at the broad H- and Ks-bands, we studied a region of 22´´ × 22´´ around the UCHii region G045.47+0.05, a massive-star forming site at a distance of about 8 kpc. To image the source with the highest spatial resolution possible we employed the adaptative optics system ALTAIR, achieving an angular resolution of about 0.15 arcsec. Results: We discovered a cone shaped nebula that has an opening angle of about 90° and extends eastward of the IR source 2MASS J19142564+1109283, which is very likely a massive young stellar object (MYSO). This morphology suggests a cavity that was cleared in the circumstellar material, and its emission may arise from scattered continuum light, warm dust, and probably also from emission lines from shock-excited gas. The nebula, which presents arc-like features, is connected with the IR source through a jet-like structure, which is aligned with the blueshifted CO outflow found in a previous study. The near-IR structure lies ~3´´ north of the radio continuum emission, revealing that it is not spatially coincident with the UCHii region. The observed morphology and structure of the near-IR nebula strongly suggest the presence of a precessing jet. We resolved the circumstellar environment (in scale of a thousand AU) of a distant MYSO, indeed one of the farthest currently known.